PERBANDINGAN KETEPATAN MENENDANG KEARAH GAWANG DENGAN MENGGUNAKAN KURA-KURA BAGIAN DALAM DAN KURA-KURA BAGIAN LUAR KELAS XI PUTRA SMA NEGERI 1 DOMPU TAHUN PELAJARAN 2018/2019: Indonesia - Ahmad Pratama, Sandi (INSPIREE: Indonesian Sport Innovation Review, 2020)
The study purpose: The sport of football consists of various forms of movement and techniques in the game. Besides that, the understanding of kicking ball techniques properly and correctly has not been mastered so that beginners still seem to just kick without knowing what is obtained from the results of these kicks. Materials and methods: In this study the total population is 100 people taken from classes XI.A, XI.B, XI.C, XI.D and from this population will be sampled in conducting research. The sample used in this study is 20%, therefore the number of samples is 20% x 100 people and so the number of samples is 20 people. Based on this comparison, it shows that the t-test result or the t-count value is smaller than the t-table Results: "Accepted based on the results. Analysis of significant data, it can be concluded that "There is a comparison of the accuracy of kicking a ball into the goal with an inner foot turtle and an outer leg turtle in male students of class. the t-test result or the t-count value is smaller than the t-table showing 2.093> -0.59 (t-count <t-table). Conclusions: Accepted based on the results. Analysis of significant data, it can be concluded that "There is a comparison of the accuracy of kicking a ball into the goal with an inner foot turtle and an outer leg turtle in male students.